2019
DOI: 10.1177/0363546519830402
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Comparison of Vertical Mattress and Cross-stitch Suture Techniques and Single- and Double-Row Configurations for the Treatment of Bucket-Handle Medial Meniscal Tears

Abstract: Background: Given the variety of suturing techniques for bucket-handle meniscal repair, it is important to assess which suturing technique best restores native biomechanics. Purpose/Hypothesis: To biomechanically compare vertical mattress and cross-stitch suture techniques, in single- and double-row configurations, in their ability to restore native knee kinematics in a bucket-handle medial meniscal tear model. The hypothesis was that there would be no difference between the vertical mattress and cross-stitc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 44 publications
0
17
0
Order By: Relevance
“…Nakama et al 21 performed a biomechanical study evaluating 10 pairs of cadaveric knees with bucket-handle tears. The knees were divided into 2 groups: group I had 10 vertical sutures, and group II had 10 vertical crossed sutures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nakama et al 21 performed a biomechanical study evaluating 10 pairs of cadaveric knees with bucket-handle tears. The knees were divided into 2 groups: group I had 10 vertical sutures, and group II had 10 vertical crossed sutures.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in the double-crossed suture group (femoral and tibial faces), the meniscal contact area and femorotibial pressure decreased compared with the single vertical suture group. 21…”
Section: Discussionmentioning
confidence: 99%
“…Previous Technical Notes have described capsular closure with sutures tied in a parallel fashion 11 ; however, studies have demonstrated the mechanical advantage of using of a cross-mattress configuration. 12 Although standard capsular closure is adequate in most cases to restore normal hip biomechanics, capsular plication is necessary in patients with excess capsular laxity or microinstability of the joint. Although early results have been promising in our clinical practice, studies reporting medium- to long-term patient-reported outcomes are necessary to validate these results.…”
Section: Discussionmentioning
confidence: 99%
“…4) are reasonable options for this tear pattern. A double-row cross-stitch configuration was recently shown to have decreased tibiofemoral contact pressure in comparison with a vertical double-row repair in a bucket-handle medial meniscal tears at time of initial repair 70. Care should be taken to alternate mattress sutures on both the superior and inferior surfaces of the meniscus to avoid a nonanatomic reduction of the tissue.…”
Section: Vertical Tearsmentioning
confidence: 99%